PEKASAM IKAN SALIMANG: WARISAN KULINER TRADISIONAL BUDAYA MELAYU - Khafifa Khairi Annisa; Lusy Sasta Myliza; Febrianty, Ellya Roza (STKIP Subang, 2026)
Pekasam fish in Malay culture demonstrates that Pekasam is a traditional fermented fish product popular among Malay communities, particularly in Southeast Asia, such as Malaysia and Indonesia. The process of making pekasam involves marinating fish with salt, roasted rice, and other ingredients, then fermenting it for a period of time. The final product has a distinctive sour taste and a strong aroma. Many also say that pekasam fish contains lactic acid bacteria produced during the curing process. Pekasam is not just a food, but also part of Malay cultural heritage. The process of making it is often a hereditary skill maintained by families. This product also has economic value, especially for rural communities who produce and sell pekasam for a living. However, traditional pekasam production is often not standardized, resulting in variable product quality.